Competition Policy and State Aid under the European Union Emissions Trading System - Rodríguez Morales, Jorge Ernesto (2015)
The interaction between competition and environmental policy is quite complex, particularly before state aids, whose control level reflects the emerging opportunity cost between both policies. In order to illustrate the potential efficiency losses or the imbalances on level playing field of competition, this article analyzes the legal, economic and political dimensions of the European Union Emissions Trading System (EU ETS) free allocation of allowances mechanism for the power generation sector.